2020
DOI: 10.1002/hbm.24910
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy treatment responsive multimodal brain networks

Abstract: Electroconvulsive therapy is regarded as the most effective antidepressant treatment for severe and treatment‐resistant depressive episodes. Despite the efficacy of electroconvulsive therapy, the neurobiological underpinnings and mechanisms underlying electroconvulsive therapy induced antidepressant effects remain unclear. The objective of this investigation was to identify electroconvulsive therapy treatment responsive multimodal biomarkers with the 17‐item Hamilton Depression Rating Scale guided brain struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The clinical characteristics of the 18 articles that were excluded from meta-analysis were partially similar to those of articles included in the meta-analysis. Among these studies ( Supplementary Table 4 ), all had a sample size of <30 subjects except for 3 studies with sample sizes of 45 (Bai et al, 2018a ), 118 (Qi et al, 2020 ), and 122 (Sun et al, 2020 ), respectively. Ten of them recruited patients with unipolar depression only, and six of them solely focused on treatment-resistant depression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical characteristics of the 18 articles that were excluded from meta-analysis were partially similar to those of articles included in the meta-analysis. Among these studies ( Supplementary Table 4 ), all had a sample size of <30 subjects except for 3 studies with sample sizes of 45 (Bai et al, 2018a ), 118 (Qi et al, 2020 ), and 122 (Sun et al, 2020 ), respectively. Ten of them recruited patients with unipolar depression only, and six of them solely focused on treatment-resistant depression.…”
Section: Resultsmentioning
confidence: 99%
“…An almost equal number of studies used bifrontal (BF), bitemporal (BT), and right unilateral (RUL) as electrode placements during ECT. Some had provision to switch to BT (Leaver et al, 2020 ; Qi et al, 2020 ; Sun et al, 2020 ) or BF (Leaver et al, 2016b ) if RUL did not provide significant improvement. Except for Leaver et al ( 2020 ) (ultra-brief pulse-wave ECT), all studies used brief pulse-wave ECT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimodal brain imaging 21,22 data of SZ (n = 238), drinkers (n = 313), smokers (n = 104), MDD (n = 260), ASD (n = 421), and ADHD (n = 244) were collected across multiple studies [23][24][25][26] . We used specific symptom scores for each disorder as a reference to guide restingstate functional MRI (fractional amplitude of low frequency fluctuations, fALFF) and structural MRI (gray matter volume, GMV) fusion analysis to identify the multimodal brain networks that were associated with symptom scores in Center for Biomedical Research Excellence (COBRE) SZ, drinkers, smokers, MDD, ASD, and ADHD separately.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, multimodal [28] brain imaging data from the Autism Brain Imaging Data Exchange (ABIDE) [29,30] were used as the discovery (ABIDE II) and replication (ABIDE I) cohorts. Cumulating evidence has demonstrated that ASD reflects fundamental differences in both brain structure and function [31][32][33], while fractional amplitude of low-frequency fluctuations (fALFF) and GMV are two representative measures of (functional magnetic resonance imaging) fMRI and (structural MRI) sMRI.…”
mentioning
confidence: 99%